Adoção de carteiras digitais como determinante da inclusão financeira em vendedores ambulantes em Cusco - Cruz Hermoza, Alfredo (2024)
Objective: To measure the influence of adopting digital wallets on the financial inclusion of street vendors in Cusco. Methods: A quantitative approach with an explanatory, prospective and analytical scope was employed. The design was non-experimental and cross-sectional. Information was collected through surveys, using a questionnaire as the instrument, which was applied to 242 participants. Data analysis was conducted using a linear regression model. Results: It was determined that the adoption of digital wallets has a significant and positive influence on financial inclusion (β = 1.938, p < 0.05); additionally, an optimal degree of determination was observed (R2 = 99 %). Regarding the dimensions of financial inclusion, a significant and positive influence of digital wallet adoption was also found (p < 0.05). Conclusion: The adoption of digital wallets has a significant and positive influence on financial inclusion; therefore, access to the financial system for marginalized sectors requires joint collaboration between financial entities and the Government to propose policies that promote financial inclusion.